Nepal : Request for an Arrangement Under the Extended Credit Facility -Press Release; Staff Report; Debt Sustainability Analysis; Staff Supplement; Statement by the Executive Director for Nepal. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2022)
The COVID-19 pandemic severely impacted Nepal's economy. Tourist arrivals collapsed, domestic activity plummeted, and remittances have been volatile. As a result, balance of payments and fiscal financing gaps emerged. After growth was lower than expected in 2019/20, a gradual resumption in economic activity and a corresponding surge in imports and related tax receipts led to higher growth and improved fiscal outturns in 2020/21. However, important fiscal and external financing needs remain to support the COVID-19 response, facilitate a continued recovery, and maintain a comfortable level of reserves.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Czech Republic